Catalyzing and learning through private sector engagement for biodiversity conservation (CAL-PSE): a strategic partnership of the Alliance of Bioversity International & the International Center for Tropical Agriculture (CIAT): Lessons learned (2017-2024) - Deboni, Fabio; Caldas, Bernardo (2025)
The publication presents a set of lessons learned during the CAL-PSE Program (2017 - 2025), whose objective was to contribute to the conservation of biodiversity in the Brazilian Amazon through the engagement of the private sector.